The effects of immigration on household services, labour supply and fertility - Agnese Romiti (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2016)
Fertility and female labour force participation are no longer negatively correlated in developed countries. Recently, the role of immigration has been put forward as a driving factor among others. Increased immigration affects supply and prices of household services, which are relevant for fertility and employment decisions. This paper analyses the effect of immigration on labour supply and fertility of native women in the UK, with a focus on the role of immigration on household services. Adopting an instrumental variable approach based on the country-specific past distribution of immigrants at regional level, I find that immigration increases female labour supply, without affecting fertility. My results show that immigration increases the size of the childcare sector, and reduces its prices, suggesting that immigrants may ease the trade-off between working and child rearing among native women. – – In den Industrieländern korreliert die Geburtenrate heutzutage nicht mehr negativ mit der Teilnahme von Frauen am Arbeitsmarkt. In aktuellen Studien wird neben anderen Faktoren ein Zusammenhang mit Immigration hergestellt. Immigration beeinflusst das Angebot und die Preise von haushaltsnahen Dienstleistungen, welche eine wichtige Rolle für die Familienplanung und die Arbeitsentscheidungen der heimischen Bevölkerung spielen. Diese Arbeit analysiert den Effekt von Immigration auf die Beschäftigungsentscheidung von Frauen im Vereinigten Königreich unter dem Gesichtspunkt der verbesserten Verfügbarkeit von haushaltsnahen Dienstleistungen. Unter Verwendung der länderspezifischen Verteilung von Immigranten über Regionen in der Vergangenheit als Instrument für die Immigration heute wird gezeigt, dass Immigration zu mehr Beschäftigung von Frauen führt, ohne die Geburtenrate negativ zu beeinflussen. Desweiteren lässt sich zeigen, dass Immigration die Verfügbarkeit und den Preis von Angeboten im Bereich der Kinderbetreuung verbessert. Diese Ergebnisse deuten darauf hin, dass Immigration für Frauen in der heimischen Bevölkerung zu einer verbesserten Vereinbarkeit von Beruf und Familie führt.
Keywords: D10; F22; J13; J22; J61; 330; Labour Supply; Fertility; Immigration; Child Care